Shoulder dystocia: resolution proposals according to the different birthing positions depending on the mobility of the pelvis - Espinoza, Marisa Mabel (2023)
Introduction: Shoulder dystocia is a complication of vaginal delivery caused by a difficulty in delivering the fetal shoulders. It can be triggered in an unpredictable and unplanned manner, so it should be considered as a potential risk for every vaginal birth. Most of the recommendations on shoulder dystocia resolution maneuvers are made from the lithotomy position and without considering the intrinsic movements of the pelvis during labor. Objectives: To analyze the maneuvers for resolving shoulder dystocia based on knowledge of the biomechanics of the pelvis and its relationship with the fetal shoulders, considering the different birthing positions. Methods: Non-systematized bibliographic review. Results: In the case of anterior shoulder dystocia, the McRoberts maneuver with suprapubic pressure followed by extraction of the posterior arm could be recommended for a birthing woman in lithotomy position. If the birthing woman is in an upright position, it is suggested to move to the four-support position and an original variant resulting from the analysis of the biomechanics of the pelvis called ‘four-lying in asymmetry’. These maneuvers are non-invasive techniques, require minimal training and resources, and can be performed from any childbirth position. Conclusions: The resolution of shoulder dystocia does not have a single algorithm; it will depend on the type of dystocia, the position of the birthing woman, the context, and the greater or lesser ability of one maneuver over another. Gaskin maneuver and four supports in asymmetry should be considered before performing internal maneuvers for the resolution of shoulder dystocia.